Influence of lifelong cumulative HIV viremia on long-term recovery of CD4+ cell count and CD4+/CD8+ ratio among patients on combination antiretroviral therapy. (13th March 2015) - Seng, Rémonie; Goujard, Cécile; Krastinova, Evguenia; Miailhes, Patrick; Orr, Sylvie; Molina, Jean-Michel; Saada, Matthieu; Piroth, Lionel; Rouzioux, Christine; Meyer, Laurence
Abstract : Objective: We explored the impact of lifelong cumulative HIV viremia on immunological recovery during antiretroviral therapy, according to the timing of treatment initiation. Methods: We estimated lifelong cumulative HIV viremia in patients followed in the ANRS PRIMO cohort since primary infection, including 244 patients who started treatment during PHI and had at least one treatment interruption, and 218 patients who started treatment later but with no interruptions. The impact of cumulative viremia on current immunological status was analysed using linear and logistic regression models. Results: At the last visit on treatment, median CD4 + cell count was 645 cells/μl in the early/intermittent treatment group (median time from infection 9.5 years, 4.8 years of continuous treatment since last resumption), and 654 cells/μl in the deferred/continuous treatment group (median time from infection 6.1 years, 3.0 years of continuous treatment). Only 36.1 and 39.8% of patients achieved a CD4 + /CD8 + ratio of more than 1, respectively. Current CD4 + cell count was not associated with cumulative HIV viremia in either group. In contrast, patients with high cumulative HIV viremia (>66th percentile vs. <33rd percentile) were less likely to achieve a CD4 + /CD8 + ratio of more than 1 (26.8 vs. 43.3%, P  = 0.003), even after controlling for the baseline CD4 + /CD8 + ratio, treatment duration, sex and age. Much higher CD4 + cell count and CD4 + /CD8 + ratio were reached in early/continuous treatment, that is low viremia exposure group. Conclusion: Our results underline the critical need in early-treated patients to maintain adherence, in order to limit cumulative HIV viremia and optimize immunological recovery, notably the CD4 + /CD8 + ratio.